HDAC6 mediates an aggresome-like mechanism for NLRP3 and pyrin inflammasome activation - Magupalli, Venkat Giri (Science, 2020)
Inflammasomes are supramolecular complexes that play key roles in immune surveillance. This is accomplished by activating inflammatory caspases, which lead to the proteolytic maturation of IL-1β and pyroptosis. Here, we show that NLRP3- and pyrin-mediated inflammasome assembly, caspase activation, and IL-1β conversion occur at the microtubule-organizing center (MTOC). Furthermore, the dynein adaptor HDAC6 is indispensable for the microtubule transport and assembly of these inflammasomes, shown by chemical inhibition and targeted deletion in immortalized and primary macrophages and in mice. Because HDAC6 can transport ubiquitinated pathological aggregates to the MTOC for aggresome formation and autophagosomal degradation, its role in NLRP3 and pyrin inflammasome activation also offers an inherent mechanism to downregulate these inflammasomes by autophagy. This work suggests an unexpected parallel between the formation of physiological and pathological aggregates.